NILAI-NILAI PENDIDIKAN ISLAM DALAM FILM ANIMASI NUSSA DAN RARA KARYA ADITYA TRIANTORO - Moch. Eko Ikhwantoro; Abdul Jalil; Ach. Faisol (VICRATINA, 2019)
This study aims to determine the educational values contained in the animated film Nussa and Rara by Aditya Triantoro, the focus of research is 1) the value of Islamic education, 2) the concept of Islamic education, and 3) the relevance of Nussa and Rara's animated film in Islamic education. This type of research is a library study (library reseach), using a qualitative descriptive approach. Data collection is done with documentation and as for data obtained from primary data secondary data. Data analysis techniques use content analysis. The results of this study, 1) the value of aqidah education, the value of shari'a education, and the value of moral education in the Nussa and Rara Animation film, 2) the concept of Islamic education that teaches tenderness and good behavior in delivering Islamic teachings, 3) relevance in education Islam is the goal of forming perfect beings, learning resources from the Qur'an and Hadiths, the learning component includes the education of faith, worship, and morals.